Digital Health: Tracking Physiomes and Activity Using Wearable Biosensors Reveals Useful Health-Related Information - Li, Xiao; Dunn, Jessilyn; Salins, Denis; Zhou, Gao; Zhou, Wenyu; Schüssler-Fiorenza Rose, Sophia Miryam; Perelman, Dalia; Colbert, Elizabeth; Runge, Ryan; Rego, Shannon; Sonecha, Ria; Datta, Somalee; et al. (PLOS Biology, 2017)
Author Summary A new wave of wearable sensors allows frequent and continuous measurements of body functions (physiology), including heart rate, skin temperature, blood oxygen levels, and physical activity. We investigated the ability of wearable sensors to follow physiological changes that occur over the course of a day, during illness and other activities. Data from these sensors revealed personalized differences in daily patterns of activities. Interestingly, we discovered striking changes in particular environments such as airline flights. Blood oxygen levels decreased during high-altitude flights, and this decrease was associated with fatigue. By combining sensor information with frequent medical measurements, we made two important health-related observations. First, wearable sensors were useful in identifying the onset of Lyme disease and inflammation. From this observation, we then developed a computational algorithm for personalized disease detection using such sensors. Second, we found that wearable sensors can reveal physiological differences between insulin-sensitive and insulin-resistant individuals, raising the possibility that these sensors could help detect risk for type 2 diabetes. Overall, these results indicate that the information provided by wearable sensors is physiologically meaningful and actionable. Wearable sensors are likely to play an important role in managing health.